ANALISIS KEMANDIRIAN SANTRI DAN PESANTREN : STUDI PADA KEWIRAUSAHAAN KOPERASI PONDOK PESANTREN AL - JIHAD SURABAYA - Pramana, Bambang; Fahreza Rahmadana, Rayhan; Arul Ade Kusuma, Ahmad; Rizki Murtadho, Ihab; Huda, Bakhrul (Investama : Jurnal Ekonomi dan Bisnis, 2024)
This study aims to find out how the development of entrepreneurship in the Al-Jihad Islamic Boarding School Surabaya is able to run in creating student independence and the pesantren economy. The method used in this study is descriptive qualitative. Data obtained from interviews with cooperative management chairmen and students, then made observations and were also supported by document studies relevant to this study. The results of this study show that the development of entrepreneurship in creating student independence and the pesantren economy has been carried out with the existence of the Al-Jihad Surabaya cooperative. However, there are problems such as poor management, unsuccessful market share expansion, and competition with the surrounding community that is quite tight. On the other hand, the impression of the cooperative is considered quite good seeing the various responses and support from students, leaders or the surrounding community. So in this case, strategic management is needed in the management of Islamic boarding school cooperatives in order to be able to improve the economic welfare of Al-Jihad Islamic Boarding School.